Microwave-assisted selective leaching behavior of calcium from Basic Oxygen Furnace (BOF) slag with ammonium chloride solution - Zhang, Xiang; Ma, Guojun; Tong, Zhibo; Xue, Zhengliang (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
The Basic Oxygen Furnace (BOF) slag can be potentially used in the indirect aqueous CO2 sequestration process due to the fact that it contains large amounts of basic oxides. In this study, microwave-assisted selective leaching of calcium from BOF slag with ammonium chloride solution has been investigated in order to improve the extraction efficiency of calcium ion, and reduce leaching time and the contents of impurity ions in the leachate. The results show that the major phases of BOF slag, such as Ca2SiO4, Ca3SiO5 and Ca2Fe2O5, can react with ammonium chloride solution. The microwave power has significant effects on the leaching ratio of calcium ion from the BOF slag. After microwave-assisted leaching treatment, the internal tiny cracks can be found inside the BOF slag particles. The leaching ratio of calcium ion can be up to 90% with small amounts of impurity ions existed in the leachate. The non-isothermal leaching reactions are controlled by internal diffusion and the apparent activate energies are estimated to be 6.9-26.5 kJ/mol.